PERAN PENTING MASJID DAN MAJLIS SARWAH DALAM MEMAJUKAN MASYRAKAT MELALUI PROGRAM KKN - Susanti, Mai; Maula, Fifin Nikmatul; Aisyah, Siti (Najah: Journal of Research and Community Service, 2024)
The community service program is directed at increasing the role of mosques and majlis sarwah in helping the progress of the Kaliacar community. Some issues that can be focused on are Religious Education: How mosques can become active and effective religious education centers to increase people's religious knowledge. Social Welfare: The role of majlis sarwah in raising social resources to help the poor or vulnerable groups in society. Community Economy: How mosques can empower the local economy through training programs and small businesses that involve the community. Environment: Joint efforts of mosques and majlis sarwah in campaigning for environmental awareness and implementing environmental cleanliness and sustainability programs. Through this community service program, the focus will be on implementing various activities such as: Increasing Religious Literacy: Organizing Al-Quran reading and writing programs and religious studies in mosques to increase the community's understanding of religion. Economic Empowerment Program: Organizing skills training and establishing small businesses for residents around the mosque, with support from the sarwah council. Social Assistance: Raising donations and resources through majlis sarwah to help underprivileged families and implementing social welfare programs. Increasing Environmental Awareness: Holding environmental campaigns, cleaning the area around the mosque, and encouraging environmentally friendly practices in the community. It is hoped that this program can create positive synergy between mosques, majlis sarwah and the Kaliacar community, which will ultimately have a positive impact on spiritual, economic and social development in the region.